Severinas missiveiras : narrativas sobre a invenção da vida num sertão contemporâneo - Fonseca, Lázaro Batista (2013)
As the historical text by João Cabral de Melo, even today many severinos - husbands, fathers, sons and brothers - leave the Northeast, motivated by dreams of thriving in toil and find a meaning for their existence, fleeing from a place that feels like death and going in search of another life. However, in these new times, the destination is not the city-capital, but distant and almost uninhabited regions of the country. A question arises: if to the men still remains this possibility, for the women who stay here, what is reserved? And what is expected of them? And what they expect? Through some narratives, this work aims to discuss and problematize the meetings of Severinas women, northeastern of the backlands of Sergipe, with the news and vices that the work of his men gives them and the changes it produces in the life of the place and the people. How to occupy, if they occupy, those territories and what tatics invent to better put themselves in them. How they see themselves in these places and how in them, they assign territories, between lack of the kinsman, the expectation for his return and requirements that him absence presentified.